Malodorous Gases and the Life Quality of Inhabitants in the Anthropogenic Activity Areas - Tomasz SAWOSZCZUK; Justyna SYGULA – CHOLEWINSKA; Barbara BLYSKAL (Communications of International Proceedings, 2021)
The life quality of inhabitants in the urban areas is determined by many factors like traffic, noises, and malodorous gases. The last one is especially problematic in the inhabited areas which are closed to industrial parts of town and cities. The activity of wastewater treatment plants or composting facilities are among the most burdensome industrial plants emitting odours. The main goal of work was to establish the composition of malodorous gases reported by inhabitants living in industrial part of Krakow, Płaszów, in Poland. Based on the results of surveys conducted among people living in this area of Krakow clearly indicated that there was a problem with odour nuisance at this location. These data are also confirmed by the results of olfactometry studies carried out in this area. The results of chemical and microbiological tests allowed to demonstrate in an objective manner that it is possible for odour nuisance to occur in the study area of Krakow-Płaszów and thus have an impact on the comfort and quality of life of the nearby residents.
Keywords: Odour Nuisance; GC-MS; Olfactometry; Air Quality